Chemical and material communication between the optic nerves in rats. (25th June 2015) - Yang, Shuo; He, Heng; Zhu, Ying; Wan, Xing; Zhou, Long‐Fang; Wang, Juan; Wang, Wen‐Feng; Liu, Lei; Li, Bin
Abstract: Background: To examine interactions between optic nerves. Methods: A total of 24 Sprague–Dawley rats received unilateral intravitreal injections. The rats were equally divided into four groups: group A was administered an adeno‐associated virus (AAV) carrying an exogenous gene (ND4; rAAV‐ND4); group B, AAV carrying a green fluorescent protein (GFP; rAAV‐GFP); group C, fluorogold (FG) nerve tracer dye; and group D, phosphate‐buffered saline (PBS) as a control. Two weeks later, GFP expression was evaluated in both retinas and optic nerves of group B rats after frozen sectioning. The presence of FG was also evaluated in group C optic nerves by fluorescent microscopy after frozen sectioning. Four weeks after injection, ND4 expression was evaluated in both eyes of groups A and D using western blotting and immunofluorescence. Results: FG was observed in the optic chiasm posterior segment along the optic nerve of injected eyes. Some FG reached the anterior optic nerve of the non‐injected eye. GFP fluorescence was observed only in the retina of the injected eye but not in the contralateral retina or either optic nerve. ND4 expression was significantly different between injected and non‐injected eyes but not between the non‐injected eyes in groups A and D. Conclusion: Unilaterally injected material can reach the contralateral optic nerve through axoplasmic transport. It is possible that this the only mechanism by which the optic nerves directly communicate.